Non-lethal effects of predation risk enhance long-term memory in Drosophila melanogaster - Krama, Tatjana; Krams, Ronalds; Popovs, Sergejs; Trakimas, Giedrius; Adams, Colton B.; Freeberg, Todd M.; Jõers, Priit; Contreras-Garduño, Jorge; Rantala, Markus J.; Krams, Indrikis A. (BRILL, 2025)
Predator fear can leave long-lasting impacts on the neural circuitry and behaviours of prey organisms, leading to enduring effects on memory characteristic of post-traumatic stress disorder. Previous research showed better survival in Drosophila grown with predators and, thus, stress. A better long-term memory can likely help Drosophila avoid visiting places where predators have been spotted before. We investigated the link between predator-induced stress exposure and memory retention in two groups of Drosophila. In this study, one group of Drosophila was exposed to visual and olfactory signals of spiders during the first five days of their adult stage, prior to memory testing. We found that 1 h short-term memory did not differ between experimental flies and flies in the control group, which were raised without spiders. In contrast, flies exposed to predator presence exhibited better long-term memory than control flies 24 h later. The strain of Drosophila used was found to possess a diabetes-like biochemical phenotype in a previous study, indicating metabolic shifts between glucose and lipids, which influences memory formation and retention. We show that linking long-term memory, body and brain metabolism, and predation risk-induced stress is needed to better understand the post-traumatic stress-associated biochemical and behavioural adaptations of Drosophila.